A critical analysis of tithe and seed sowing on contemporary Christianity in Nigeria - Akabike, Gladys N. (HTS teologiese studies, 2021)
The issues of tithes and seed sowing have taken a central focus in contemporary Christianity in Nigeria among the preachers. Many a time, it is assumed that tithes and seed sowing are requirements for salvation, prosperity and total well-being of the members. Making many to believe that Christianity is a money-venture business one can succeed if he knows how to hoodwink the gullible. Many have been deceived that by parting with a substantial amount of money in the name of sowing seed, their problems would be solved. Unfortunately, the person’s problem may remain the same or even be compounded. This paper evaluates the activities, attitude and their inordinate ambitions. It examines the impact of tithe and seed sowing on Christianity in Nigeria. The research method adopted for this work is the qualitative phenomenological method. The paper observed that the value of tithe and seed sowing has changed from what is prescribed in the bible to what is preached on the pulpits. The study recommends among other things, that these preachers should preach the gospel with decorum and as it were in the bible so that its influence on Nigerians will bring about a reduction in crime, corruption and other immoral activities in Nigeria.Contribution: The article is focused on the issues of tithes and seed sowing. It underscores the fact that the message of tithe and seed sowing has become a means of siphoning members and enriching the preachers. It further reveals its negative and positive impacts such as, the promotion of corruption and fraud in the church and society, contribution to the decline of morality in the church and the society, increasing crime rate and increasing poverty rate in Nigeria among others.